Cancer classification using deep learning from medical image data - Monir, Raiyan Janik; Shaon, Shoeb Islam; Noman, Syed Mohammad; Iqbal, Sahariar (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.